2022
DOI: 10.3390/curroncol29070377
|View full text |Cite
|
Sign up to set email alerts
|

Current and New Novel Combination Treatments for Metastatic Triple-Negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) has a worse prognosis and remains the most challenging breast cancer subtype to treat. This is largely related to the heterogeneity of this disease and the lack of reliable oncological targets. In this review, we discuss the current standard-of-care treatment options for metastatic TNBC, including recent advances with the use of immunotherapy, PARP inhibitors and antibody-drug conjugates. This review also explores new agents and novel combinations arising in the field for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Ongoing research on ADC drugs in combination with PARP, PD-L1 inhibitors, and other related drugs is also worth considering. 44 In addition, the proposal for low HER2 expression has expanded the indications for trastuzumab deruxtecan. With the positive conclusion of the DESTINY-Breast04 study, trastuzumab deruxtecan was approved by the US Food and Drug Administration for use in cases of low HER2 expression hormone receptor-negative populations.…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing research on ADC drugs in combination with PARP, PD-L1 inhibitors, and other related drugs is also worth considering. 44 In addition, the proposal for low HER2 expression has expanded the indications for trastuzumab deruxtecan. With the positive conclusion of the DESTINY-Breast04 study, trastuzumab deruxtecan was approved by the US Food and Drug Administration for use in cases of low HER2 expression hormone receptor-negative populations.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the management of TNBC that is unresponsive to the current treatment approaches is still a main clinical challenge and for this reason it is important to develop novel therapeutic strategies [ 3 , 50 , 51 , 52 ]. In this study, we demonstrated that zein nanoparticles can be used as biocompatible carriers for the co-delivery of the BET inhibitor JQ1 and PTX, two molecules characterized by a strong lipophilic character [ 4 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several treatment schemes for early diagnosed TNBC that are based on anthracycline and taxane administration, but which cause numerous adverse effects (nausea, fatigue, gastrointestinal toxicity, myelosuppression, alopecia, hypothyroidism, hyperthyroidism, pneumonitis, skin reactions, adrenal insufficiency, peripheral neuropathy, neutropenia, pyrexia, anemia, thrombocytopenia, electrolyte abnormalities, infection, etc.) and do not lower the relapse rate [ 50 ].…”
Section: Molecular Characteristics Of Tnbcmentioning
confidence: 99%